Pale horse rider William Cooper, the rise of conspiracy, and the fall of trust in America - Jacobson, Mark 1948- (Blue Rider Press, 2018)
"We are living in a time of unprecedented distrust in America: Faith in the government is at an all-time low, and political groups on both sides of the aisle are able to tout preposterous conspiracy theories as gospel, without much opposition. "Fake news" is the order of the day. This book is about a man to whom all of it points, the greatest conspiracist of this generation and a man you may not have heard of. A former U.S. naval intelligence worker, Milton William Cooper published his manifesto Behold a Pale Horse in 1991. Since then it has gone on to sell hundreds of thousands of copies, becoming the number-one bestseller in the American prison system.
Includes bibliographical references (pages 355-359) and index
Keywords: Cooper, Milton William; Cooper, Milton William -- 1943-2001; SOCIAL SCIENCE / Popular Culture / bisacsh; Conspiracies -- United States -- History; Paranoia -- United States -- History; SOCIAL SCIENCE / Popular Culture; Biografie